An expert system feedback tool improves the reliability of clinical gait kinematics for older adults with lower limb osteoarthritis - Osis, Sean T.; Kobsar, Dylan; Leigh, Ryan J.; Macaulay, Charles A.J.; Ferber, Reed (Gait & posture, 2017)
•An expert system to improve gait data reliability was evaluated in patients with osteoarthritis.•Significant improvement in reliability was measured for hip kinematics.•Accuracies were significantly improved for binary classifiers in both patient samples.•The expert system improves the reliability of biomechanical gait data in test-retest protocol. Recently, an expert system was developed to provide feedback to examiners with the aim of improving reliability of marker-based gait analysis. The purpose of the current study was to evaluate the effectiveness of this novel feedback tool in improving the reliability of gait analysis for individuals with lower limb osteoarthritis. Three-dimensional gait analysis was conducted for n=27 individuals, at two different time points, and during each session the feedback tool was used to refine marker placement. Results for both discrete variables and support vector machine classifications demonstrated improved reliability of the data with the feedback tool.